Agreement between Mongolia and Japan for cultural relation, its historical significance - B, Serjav (Journal of International Studies, 2018)
In this article, we aimed to discuss history of establishing an agreement on cultural cooperation between Mongolia and Japan, some factors affected on it, commencement and progress of cooperation, and implementation outcomes. Within framework of the agreement, the relationship developed with Japan have been high importance to the deepening of mutual-understanding and developing of friendship at all sectors, and moreover, we assume that it has been one of the important basis to the expansion of Mongolian–Japanese relationships up to date, and would still continue to inspire in further.